Maths Revision

HideShow resource information
  • Created by: Laurent10
  • Created on: 13-03-16 14:47
Solve the equation x2-6x-2=0
Completing the square, x2-6x-2=0, b/2= 3, 3 squared= 9 x2-6x+9-2-9=0, split whole thing into 2 parts, now x2-6x+9 is solvable, equals (x+3) squared-11. Add 11 to both sides=(x+3) squared equals 11, square root both sides is 3 plus or minus square 11
1 of 5
dv v h
dgh
2 of 5
gb
rg
3 of 5
egtreey
bg5y4b
4 of 5
tg
556
5 of 5

Other cards in this set

Card 2

Front

dv v h

Back

dgh

Card 3

Front

gb

Back

Preview of the front of card 3

Card 4

Front

egtreey

Back

Preview of the front of card 4

Card 5

Front

tg

Back

Preview of the front of card 5

Comments

No comments have yet been made

Similar Mathematics resources:

See all Mathematics resources »See all Quadratic equations resources »